If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -25y + -55 = 0 Reorder the terms: -55 + -25y = 0 Solving -55 + -25y = 0 Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '55' to each side of the equation. -55 + 55 + -25y = 0 + 55 Combine like terms: -55 + 55 = 0 0 + -25y = 0 + 55 -25y = 0 + 55 Combine like terms: 0 + 55 = 55 -25y = 55 Divide each side by '-25'. y = -2.2 Simplifying y = -2.2
| 30-2k=20 | | -12x-6=0 | | F(x)=cos(9x) | | 2a-10=9a+11 | | 3(2x-5)27= | | 3(X-2)+5=2(5x+4) | | 136-4x= | | -2x+12-4x= | | 3+2g=7-6g | | 3^2=1/81 | | 13x+8=5x | | 2.4c=48 | | f(x)=3x^2-363 | | (x-1)-x(3x-2)=0 | | x+3y=600 | | 0.5x^2+1.5x-54=0 | | x+(n+80)=400 | | y=8sin(x)+15 | | 3y-6x=8 | | 3x+x=4200 | | 16-n+35=42 | | x^2+2x+2=2x^2+2x | | 3S+4=-6 | | 12x^2-10=48 | | S=1.06-0.325s | | X=5+-0.25x | | 26+17-n=28 | | 3/h=9/3h | | 10x+5+12x-1=90 | | 10x+5+12-1=90 | | a+3-6a=13 | | -2z+4z=3z+5+2 |